The Clustering of Luminous Red Galaxies at z similar to 0.7 from EBOSS and BOSS Data - Zhai, Zhongxu (2017)
We present the first scientific results from the luminous red galaxy (LRG) sample of the extended Baryon Oscillation Spectroscopic Survey (eBOSS) combined with the high-redshift galaxies of the previous BOSS sample. We measure the small-and intermediate-scale clustering from a sample of more than 97,000 galaxies in the redshift range 0.6 < z < 0.9. We interpret these measurements in the framework of the Halo Occupation Distribution. The bias of this sample of LRGs is 2.30 +/- 0.03, with a satellite fraction of 13% +/- 3% and a mean halo mass of 2.5 x 10(13)h(-1)M(circle dot). These results are consistent with expectations, demonstrating that these LRGs will be reliable tracers of large-scale structure at z similar to 0.7. The galaxy bias implies a scatter of luminosity at fixed halo mass, sigma(log) L, of 0.19 dex. Using the clustering of massive galaxies from BOSS CMASS, BOSS LOWZ, and SDSS, we find that sigma(log) L = 0.19 is consistent with observations over the full redshift range that these samples cover. The addition of eBOSS to previous surveys allows the investigation of the evolution of massive galaxies over the past similar to 7 Gyr.